Development of Science Literacy-Based Physics e-Module in Kinematics Motion - Kholiq, Abd.; Sucahyo, Imam; Anggaryani, Mita (FKIP Universitas Lampung, 2022)
The purpose of this study is to describe the feasibility of the e-Module Based on Science Literacy (e-MLIST) in the Basic Physics course on the topic motion kinematics. The eMLIST media could be the answer to the paradigm shift in the world of education during COVID-19. This study applied research and development with the Decide, Design, Develop, and Evaluate (DDDE) model to create the electronic modules. The e-MLIST has several advantages, such as the Module being electronic-based, which offers flexible utility. It means eMILST can be used whenever and wherever it is located. The e-MILST could be used to train students' scientific literacy skills in Basic Physics One lecture on motion kinematics. In this case, e- MILST will be used as a source of learning and teaching materials in the Basic Physics One course, whether offline, online or hybrid. The analysis results show that the e-MLIST is very valid, with 91.69% validity, The practicality of using e-MLIST in basic physics lectures 1 motion kinematics material is 87.13% with excellent criteria and The effectiveness of the use of e-MLIST in basic physics lectures 1 motion kinematics material is seen from the improvement of students' science literacy skills by n-gain 0.57 with moderate criteria. This means that eMILST is worthy of being used as a learning media in basic physics lectures 1 topic of motion kinematics. Keywords: e-module, science literacy, physics learning. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1572-1582